Legal Protection Strategies for Underage Victims of Bullying and How to Prevent it in Elementary School Environments - Firdausa, Salsabila (Proceedings Series on Social Sciences & Humanities, 2023)
Bullying is a repeated negative behavior that intends to cause displeasure or pain by others, either one or several people directly against someone who is unable to resist it. Forms of behavioral deviations that occur in elementary school students are not only in the form of violence but also forms of aggressive behavior. In fact, things that are considered normal behavior by elementary school children are sometimes classified as behavioral deviations. Starting from just mocking their friends, hitting, pinching, and others. Teachers assume that school bullying behavior that occurs is a process of student development and there is no follow-up from teachers to overcome the problem of school bullying behavior that occurs in schools so that school bullying behavior occurs more often repeatedly due to the lack of response from teachers to school bullying behavior that occurs in the classroom and school environment. The purpose of this study is to determine the implementation of legal protection for underage victims of bullying in the elementary school environment and what obstacles affect it in terms of applicable laws and regulations. This research uses a juridical approach. The types and sources of data consisting of primary data sourced from the field, in the form of interviews and observations. Based on the results of research that has been conducted by the author, the research is analyzed using the empirical juridical approach method. From this research, it can be concluded that many educators do not know the regulations regarding bullying and there are no obstacles to schools to teach bullying actions so that many bullying activities occur in schools.